Changing on the Inside: Restorative Justice in Prisons: A Literature Review - Wallace, Rebecca M.; Wylie, Karen (International Journal of Bahamian Studies, 2013)
In recent years there has been increasing interest in the use of restorative justice, including its use within the prison environment. This literature review first considers some of the theory and practice of restorative approaches in general terms before turning to consider their application in the Bahamian and wider Caribbean setting, particularly Jamaica and Trinidad and Tobago. The literature review was undertaken collaboratively with the College of The Bahamas faculty involved in a profiling study of the inmates held at Her Majesty’s Prison Fox Hill, Nassau. The findings of that study relating to restorative justice are referred to in the review of sources.